The quality of life of Muar river community and socio-economic factors that impinge it - Md. Yassin, Sulaiman; Mohamed Shaffril, Hayrol Azril; Hassan, Md. Salleh; Othman, Mohd Shahwahid; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi (American-Eurasian Network for Scientific Information, 2010)
Quality of life is indeed an important contributor for rural community development in Malaysia and this study would like to investigate the quality of life of the community who are living near to the one of the major rivers in Malaysia; The Muar River. This is a quantitative study, through a simple random sampling, a total of 150 people who live near to Muar River have been selected as the respondents. To gain the data needed, respondents were questioned through face to face interviews based on the developed and tested questionnaire. The results indicated that Muar River community has a high level of quality of life. Further analysis has revealed that aspect of home conditions and social involvement and relationship recorded the highest scores. Inferential analyses performed through ANOVA and Pearson product-moment correlation have revealed that income was the only factor that has a significant difference and significant relationship with quality of life. It is suggested that income generating activities such as boat renting, hotel, home-stay and local product shops be established along Muar River. Furthermore, responsible ministries and agencies can promote and advertise Muar River as one of the main tourism attractions in Malaysia.